Globalização, regulação e neonacionalismo: uma análise das agências reguladoras - BOTELHO, Antonio José Junqueira (Revista de Sociologia e Política, 2002)
A liberalização da economia e a reforma do Estado dos anos 90 pareciam ter definitivamente relegado às paginas da história o nacionalismo industrial, marco da economia política brasileira no pós-guerra. Este, entretanto, experimenta um renascimento desde o limiar da década de 1990. Este trabalho busca entender a natureza do ressurgimento desse neonacionalismo tecnológico e industrial no bojo de agências reguladoras com elevado grau de autonomia cujas principais missões são a defesa da competição e do consumidor. Suas conclusões sugerem que as condições para seu ressurgimento estão ligadas à manutenção, nessas agências, de elites técnicas oriundas das instituições governamentais que lideravam o padrão desenvolvimentista, em conjunção com uma crescente regionalização de demandas, por sua vez decorrentes de pressões por um novo pacto federativo em uma conjuntura de crise. Abstract The liberalization of the economy and State reforms of the nineties initially seemed to have left industrial nationalism ¾ the framework adopted by post-war Brazilian political economy ¾ to the annals of history. However, this perspective has undergone a certain rebirth since the beginning of the nineties. This paper seeks an understanding of this rebirth of technological and industrial neo-nationalism within highly autonomous regulatory agencies whose principal mission is the defense of competition and the consumer. My conclusions suggest that the conditions for this reemergence are linked to the way in which these agencies have maintained the technical elites from governmental institutions who were at the forefront of the developmentalist project, in conjunction with the increased regionalization of demands that has been the result of pressures for a new federative pact deriving from conditions of crisis. The liberalization of the economy and State reforms of the nineties initially seemed to have left industrial nationalism ¾ the framework adopted by post-war Brazilian political economy ¾ to the annals of history. However, this perspective has undergone a certain rebirth since the beginning of the nineties. This paper seeks an understanding of this rebirth of technological and industrial neo-nationalism within highly autonomous regulatory agencies whose principal mission is the defense of competition and the consumer. My conclusions suggest that the conditions for this reemergence are linked to the way in which these agencies have maintained the technical elites from governmental institutions who were at the forefront of the developmentalist project, in conjunction with the increased regionalization of demands that has been the result of pressures for a new federative pact deriving from conditions of crisis. Résumé La libéralisation de l’économie et la réforme de l’État dans les années 90 étaient censées avoir définitivement renvoyé aux pages de l’histoire le nationalisme industriel, point de repère de l’économie politique brésilienne dans l’après-guerre. Pourtant ce nationalisme semble renaitre depuis le début des années 90. Ce travail essaye de comprendre la nature de la réapparition de ce néonationalisme technologique et industriel au sein des agences régulatrices et du monde des consommateurs. Les conclusions suggèrent que les conditions contribuant à son retour sont liées à la manutention, dans ces agences, des élites techniques originaires des institutions gouvernementales qui prônaient la voie du développement, avec une croissante régionalisation de la demande, qui à son tour découlait des pressions en faveur d’un nouveau engagement de la fédération dans une conjoncture de crise.